2016
DOI: 10.1111/jocn.13441
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap in sexual healthcare in nursing practice: implementing a sexual healthcare training programme to improve outcomes

Abstract: The training programme could reduce challenges related to sexual healthcare issues in nursing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 37 publications
(64 reference statements)
1
41
1
3
Order By: Relevance
“…Sample sizes ranged from 9 (Klaeson et al, ) –477 (Krouwel et al, ). Two studies evaluated the effectiveness of sexual healthcare training programmes for student nurses (Jonsdottir et al, ; Sung et al, ). A majority of the studies were conducted to explore and describe nurses’ attitudes, knowledge, experiences and barriers in regard to discussing sexuality and sexual health care with patients (Arikan et al, ; Hoekstra, Lesman‐Leegte, Couperus, Sanderman, & Jaarsma, ; Huang, Tseng, & Lee, ; Klaeson et al, ; Krouwel et al, ; Moore, Higgins, & Sharek, ; Saunamäki & Engström, ; Sung, Huang, & Lin, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sample sizes ranged from 9 (Klaeson et al, ) –477 (Krouwel et al, ). Two studies evaluated the effectiveness of sexual healthcare training programmes for student nurses (Jonsdottir et al, ; Sung et al, ). A majority of the studies were conducted to explore and describe nurses’ attitudes, knowledge, experiences and barriers in regard to discussing sexuality and sexual health care with patients (Arikan et al, ; Hoekstra, Lesman‐Leegte, Couperus, Sanderman, & Jaarsma, ; Huang, Tseng, & Lee, ; Klaeson et al, ; Krouwel et al, ; Moore, Higgins, & Sharek, ; Saunamäki & Engström, ; Sung, Huang, & Lin, ).…”
Section: Resultsmentioning
confidence: 99%
“…Three other studies that used different study designs (mixed method, interventional and cross‐sectional survey) researched the same population of nurses (oncology) and concluded nurses who provided their patients with sexual healthcare education had a higher level of knowledge of sexual health due to years of nursing experience, recent training in the past 5 years and/or are graduate prepared (Jonsdottir et al, ; Krouwel et al, ; Moore et al, ). However, in two studies, nurses reported a lack of education, in‐service and training about sexual health that lead to knowledge and skill deficits in providing sexual healthcare information (Jonsdottir et al, ; Sung et al, ). Nurses were willing and wanted more knowledge, in‐services and training to engage in more meaningful conversations with patients (Jonsdottir et al, ; Saunamäki & Engström, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of knowledge and awareness is most likely a result of insufficiency in the current educational system; an omission recognized by nurses both nationally and internationally (Hautamaki, Miettinen, Kellokumpu‐Lehtinen, Aalto, & Lehto, ; Ho & Fernandez, ). Present findings, endorsed by literature, emphasize the necessity of implementing adequate education and training for nurses to incorporate sexual care into daily practice (East & Hutchinson, ; Sung, Jiang, Chen, & Chao, ; Sung & Lin, ). However, little is known about the long‐term effectiveness of the implementation of sexual education and training and if the renewed skills and practice patterns will sustain over time (Sung & Lin, ).…”
Section: Discussionmentioning
confidence: 70%